Efforts to Improve Learning Achievement in Civic Education Through Problem Based Learning Models - Pangalila, Theodorus; Usman, Irawan; Rattu, Jan A. (Technium Education and Humanities, 2024)
The purpose of this research is to determine whether the use of the Problem Based Learning (PBL) learning model can improve Civic learning achievement in class VII students at SMP Negeri Satu Atap Malangga for the 2022/2023 academic year. This research approach is Classroom Action Research. The research location was SMP Negeri Satu Atap Malangga with the research sample being class VII students totaling 30 students. The data collection techniques used were tests, observations, questionnaires, interviews, and documentation. The data from the research in the field were processed and analyzed qualitatively. This Classroom Action Research was conducted in 2 (two) cycles. Each cycle consists of 4 (four) stages, namely: (1) action planning, (2) action implementation, (3) observation and interpretation, and (4) analysis and reflection. The results showed that the application of the Problem-based learning model can improve the learning achievement of Civics class VII students of SMP Negeri Satu Atap Malangga on the basic competencies of describing the nature of norms, habits, customs, regulations that apply in society. This can be shown in the increase in students’ learning achievement from before the implementation of the action, cycle I, and cycle II. Before the implementation of the action, the completeness of the students’ learning outcomes was 5 people complete with a percentage of 16.7% and a class average of 53.5. Cycle I the completeness of students’ learning outcomes increased to 16 people with a percentage of 53.3%, the class average increased to 69.7. Cycle II increased again to 26 people with a percentage of 86, 7%, the class average increased again to 81.6. This figure exceeds the predetermined target of 85%, so it can be concluded that the target of 85% completeness of student learning outcomes has been achieved in cycle II. The application of the Problem Based Learning learning model can also increase the activeness of students in class VII SMP Negeri Satu Atap Malangga on the basic competencies of describing the nature of norms, habits, customs, rules that apply in society. This can be shown in the achievement of all targeted items, which is 65%. In cycle I, the target of 65% for all items has not been achieved, because there are still six items that have not reached the 65% target, but in cycle II the target set can be achieved.